2008
DOI: 10.1071/ea07033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition from mid to late pregnancy on the performance of twin- and triplet-bearing ewes and their lambs

Abstract: This experiment was conducted to determine the effect of two different feeding levels on ewes during mid and late pregnancy on lamb birthweight and growth to weaning. Twin- and triplet-bearing Romney ewes (n = 80 and 56, respectively) were allocated to one of two feeding regimes and provided pastures with an average sward height of less than 2 cm (~700 kg dry matter/ha) or greater than 4 cm (~1300 kg dry matter/ha). Ewes were allocated to these feeding regimes during mid pregnancy (day 70–107 of pregnancy; P70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The mobilization of body fat reserves is indicated by elevated plasma concentrations of NEFA and βHB (Robinson et al, 2002b). In previous studies (Corner et al, 2008;Tygesen et al, 2008;Álvarez-Rodríguez et al, 2012) where ewes received a restricted plane of nutrition during late gestation, increasing plasma NEFA concentrations were observed in conjunction with a decline in BCS. Therefore, in the present study, the lack of difference in ewe plasma NEFA concentrations was unexpected.…”
Section: Discussionmentioning
confidence: 92%
“…The mobilization of body fat reserves is indicated by elevated plasma concentrations of NEFA and βHB (Robinson et al, 2002b). In previous studies (Corner et al, 2008;Tygesen et al, 2008;Álvarez-Rodríguez et al, 2012) where ewes received a restricted plane of nutrition during late gestation, increasing plasma NEFA concentrations were observed in conjunction with a decline in BCS. Therefore, in the present study, the lack of difference in ewe plasma NEFA concentrations was unexpected.…”
Section: Discussionmentioning
confidence: 92%
“…Previous hogget pastoral studies Kenyon et al 2008b;Mulvaney et al 2008Mulvaney et al , 2010 have shown that under similar herbage levels, the live weight of the lamb was not affected by herbage intake. Also, pastoral studies by and Corner et al (2008) involving twin lambs born to mature multiparous ewes reported that similar nutritional levels did not affect the lamb weaning live weights. This suggests that nutrition during pregnancy does not affect lamb live weight during lactation of twin lambs born to hoggets.…”
Section: Discussionmentioning
confidence: 99%
“…In twin-bearing mature multiparous ewes, increasing the level of pastoral nutrition from mid-pregnancy to parturition increased lamb birth weight under New Zealand pastoral conditions Corner et al 2008). This supports the results obtained in the present study from hoggets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations